Lamotrigine Augmentation of Serotonin Reuptake Inhibitors in Severe and Long-Term Treatment-Resistant Obsessive-Compulsive Disorder. (14th July 2013) - Arrojo-Romero, Manuel; Tajes Alonso, María; de Leon, Jose
Abstract : The treatment recommendations in obsessive-compulsive disorder (OCD) after lack of response to selective serotonin reuptake inhibitors (SSRIs) include augmentation with other drugs, particularly clomipramine, a more potent serotonin reuptake inhibitor (SRI), or antipsychotics. We present two cases of response to lamotrigine augmentation in treatment-refractory OCD; each received multiple SRI trials over a >10-year period. The first patient had eleven years of treatment with multiple combinations including clomipramine and SSRIs. She had a >50% decrease of Y-BOCS (from 29 to 14) by augmenting paroxetine (60 mg/day) with lamotrigine (100 mg/day). The second patient had 22 years of treatment with multiple combinations, including combinations of SSRIs with clomipramine and risperidone. She had an almost 50% decrease of Y-BOCS (from 30 to 16) and disappearance of tics by augmenting clomipramine (225 mg/d) with lamotrigine (200 mg/day). These two patients were characterized by lack of response to multiple treatments, making a placebo response to lamotrigine augmentation unlikely. Prospective randomized trials in treatment-resistant OCD patients who do not respond to combinations of SSRIs with clomipramine and/or antipsychotics are needed, including augmentation with lamotrigine. Until these trials are available, our cases suggest that clinicians may consider lamotrigine augmentation in such treatment-resistant OCD patients.